Intertextuality in the Tafsir Ya Ayyuha Al-Lazina Amanu by Syaikh Abdul Latief Syakur - Wahidi, Ridhoul (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2024)
This study examines the intertextual approach of Syaikh Abdul Latief Syakur in his Tafsir Yā Ayyuha Al-Lażīna Āmanū, focusing on how he engages with classical Islamic sources and contextualizes them within his socio-historical milieu. The library research method includes codicological analysis of the manuscript to examine its physical attributes, while also analyzing the textual connections between Tafsir Yā Ayyuha Al-Lażīna Āmanū and its primary intertextual sources. Key findings highlight three main intertextual strategies in Syaikh Abdul Latief Syakur’s work: transformation, where classical interpretations are adapted to address ethical and linguistic nuances; expansion, where Qur’anic terms are recontextualized to reflect universal Islamic principles; and parallelism, which identifies recurring themes and structures across verses to illustrate the coherence of Qur’anic discourse. The study also explores the use of primary sources, including Anwār al-Tanzīl wa Asrār al-Takwīl by al-Baidlawi, Tanwīr al-Miqbās min Tafsīr Ibn ‘Abbās, and references to the Torah, illustrating how these works informed his interpretations. By integrating these sources with his unique scholarly perspective, Syaikh Abdul Latief Syakur provides a tafsir that bridges classical traditions and contemporary concerns.